Trifluoromethylphenylacetic Acid as In Situ Accelerant of Ostwald Ripening for Stable and Efficient Perovskite Solar Cells. Issue 5 (30th March 2021) - Zhu, Hepeng; Duan, Chenghao; Qin, Minchao; Liu, Zidan; Li, Jiong; Yuan, Ligang; Wen, Qiaoyun; Lu, Xinhui; Shi, Lei; Xie, Jiangsheng; Yan, Keyou
Abstract : Perovskite thin film quality, including large grain size and low defect, is one of the fundamental factors to improve the performance and stability of perovskite solar cells (PSCs). Herein, trifluoromethylphenylacetic acid (TFPA) as the accelerant of Ostwald ripening is introduced and an in situ crystal growth control (ICGC) strategy is developed to obtain high‐quality thin films. With adding a proper amount of TFPA into the FAI/MAX (X is Br and Cl) precursor in the two‐step method, the larger grain size and reduced defect density perovskite are achieved due to Ostwald ripening. The ICGC process makes the average particle size from 476 to 625 nm. The defect density is reduced by a factor of 3.18. The high‐quality thin film endows the champion PSC (SnO2 /perovskite/spiro‐OMeTAD) with a power conversion efficiency (PCE) of champion PSC higher than 22.19%. Furthermore, TFPA is insoluble in the water and thus TFPA‐modified film is resistive to moisture. The device can be stored in an argon glove box for 2000 h without efficiency change and when exposed to 65–75% relative humidity for more than 1500 h, it retains more than 85% of the initial PCE. Abstract : An in situ crystal growth control (ICGC) strategy is developed with trifluoromethylphenylacetic acid (TFPA) as the accelerant of Ostwald ripening to obtain high‐quality perovskite films. The high‐quality perovskite film endows the champion perovskite solar cell with a power conversion efficiency higher than 22.19%. The hydrophobic property of TFPA can effectively prevent the erosion of device by moisture.